Ayodhya - Bakker, H., (Asian Studies - Book Archive pre-2000., 1986)
Three parts in one Volume (Pt. I: The History of Ayodhya from the 7th century BC to the middle of the 18th century; its development into a sacred centre with special reference to the Ayodhyamahatmya and to the worship of Rama according to the Agastyasamhita. Pt. II: Ayodhyamahatmya. Introduction, Edition, and Annotation. Pt. III: Appendices, Concordances, Bibliography, and Indexes). With illustrations and 5 maps.